Strategies to manage hepatitis C virus (HCV) infection disease burden – volume 2. (January 2015) - Gane, E.; Kershenobich, D.; Seguin‐Devaux, C.; Kristian, P.; Aho, I.; Dalgard, O.; Shestakova, I.; Nymadawa, P.; Blach, S.; Acharya, S.; Anand, A. C.; Andersson, M. I.; et al.
Summary: The hepatitis C virus (HCV) epidemic was forecasted through 2030 for 15 countries, and the relative impact of two scenarios was considered: (i) increased treatment efficacy while holding the treated population constant and (ii) increased treatment efficacy and increased annual treated population. Increasing levels of diagnosis and treatment, in combination with improved treatment efficacy, were critical for achieving substantial reductions in disease burden. In most countries, the annual treated population had to increase several fold to achieve the largest reductions in HCV‐related morbidity and mortality. This suggests that increased capacity for screening and treatment will be critical in many countries. Birth cohort screening is a helpful tool for maximizing resources. In most of the studied countries, the majority of patients were born between 1945 and 1985.